2008
DOI: 10.1165/rcmb.2007-0294oc
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Co-Activates Interleukin-8 Transcription

Abstract: The heat shock (HS) response is a phylogenetically ancient cellular response to stress, including heat, that shifts gene expression to a set of conserved HS protein (HSP) genes. In our earlier studies, febrilerange hyperthermia (FRH) not only activated HSP gene expression, but also increased expression of CXC chemokines in mice, leading us to hypothesize that the CXC chemokine family of genes might be HSresponsive. To address this hypothesis we analyzed the effect of HS on the expression of IL-8/CXCL-8, a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 36 publications
(45 reference statements)
11
66
0
1
Order By: Relevance
“…We and others have demonstrated that elements of the HS response are activated at febrile-range temperatures and regulate genes involved in inflammation and the innate immune response, including tumor necrosis factor α (Ostberg et al 2000;Singh et al 2002Singh et al , 2000, interleukin (IL)-1β (Cahill et al 1996;Fairchild et al 2000), IL-8, and granulocyte macrophage colony-stimulating factor (Rice et al 2005;Singh et al 2008), as well as HSPs. A computerassisted analysis of CXC chemokine promoters showed that almost every member of this family of neutrophil chemotaxins contains HSEs within their promoter sequences, suggesting these genes may be a newly recognized class of HSF-1-regulated genes (Nagarsekar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that elements of the HS response are activated at febrile-range temperatures and regulate genes involved in inflammation and the innate immune response, including tumor necrosis factor α (Ostberg et al 2000;Singh et al 2002Singh et al , 2000, interleukin (IL)-1β (Cahill et al 1996;Fairchild et al 2000), IL-8, and granulocyte macrophage colony-stimulating factor (Rice et al 2005;Singh et al 2008), as well as HSPs. A computerassisted analysis of CXC chemokine promoters showed that almost every member of this family of neutrophil chemotaxins contains HSEs within their promoter sequences, suggesting these genes may be a newly recognized class of HSF-1-regulated genes (Nagarsekar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed in a passive lysis buffer (Promega), and firefly luciferase and Renilla luciferase activities were measured using the DualLuciferase Reporter Assay System (Promega). Renilla luciferase was used for normalization, and all values were further standardized to medium-treated pcDNA3-YFP-hTLR2 transfectants to determine relative luciferase units (47).…”
Section: Methodsmentioning
confidence: 99%
“…For immunoblotting, the membranes were blocked with 5% nonfat dry milk in TTBS (25 mM Tris, pH 7.4, 0.5 M NaCl, 0.05% Tween 20) and probed using the following antibodies: Hsp70 (StressGen, Ann Arbor, MI), ␤-tubulin (Millipore/Chemicon, Bellerica, MA), HSF1, phospho-ERK, phospho-ribosome S6 kinase (RSK), and their total forms from Santa Cruz Biotechnology (Santa Cruz, CA) and total and p38␣, phospho-p38 and phospho-MAP kinase-activated protein kinase-2 (MK2) were obtained from Cell Signaling (Danvers, MA). Bands were developed using HRP-conjugated appropriate secondary antibody (Santa Cruz) and ECL detection system (Pierce, Thermo Fisher) and quantified using a gel documentation system (Fuji LAS-4000) as described earlier (33,36,37).…”
Section: Methodsmentioning
confidence: 99%
“…RNA Extraction and Quantitative Real Time PCR-Total RNA from RAW cells was isolated using a Qiagen kit, contaminating DNA eliminated using DNase I digestion, and RNA was reverse transcribed using oligo(dT) primers and a cDNA synthesis kit according to the manufacturer's protocol (Promega, Madison, WI) as we have previously described (36,37). Duplicate 25-l real time PCRs were performed in 96-well plates using a SYBR-Green reaction mix (Bio-Rad) and a Bio-Rad iCycler IQ optical module according to the supplier's protocol with the following forward and reverse primers: GAPDH, 5Ј-agcctcgtcccgtagacaaaat and 5Ј-tggcaacaatctccactttgc; and HSPA1A, 5Ј-ggccagggctggattact and 5Ј-gcaaccaccatgcaagatta.…”
Section: Methodsmentioning
confidence: 99%